Use of lipid-lowering drugs in restricted health access settings: Results from the trends in drug utilization during covıd-19 pandemic in Turkey (PANDUTI-TR) study - Vızdıklar, Caner; Aydın, Volkan; Tazegül, Gökhan; Kaşkal, Mert; Akıcı, Ahmet (My University, 2024)
Background: COVID-19 restrictions prompted changes in chronic disease management and lifestyle modifications, potentially altering cardiometabolic indicators and lipid-lowering pharmacotherapy patterns. We aimed to assess lipid-lowering drug (LLD) utilization trends during COVID-19 restrictions. Methods: We obtained nationwide outpatient drug sales and prescribing data for 01.03.2018–31.12.2022 from IQVIA™ Turkey. We evaluated average monthly LLD consumption, their costs, and quarterly prescribing levels in three periods: “before restrictions” (BfR, 01.03.2018–31.03.2020), “during restrictions” (DuR, 01.04.2020–31.03.2022), and “after restrictions” (AfR, 01.04.2022–31.12.2022). Drug utilization was measured via “defined daily dose/1000 inhabitants/day” (DID) metric. Results: LLD utilization increased from 25.4 ± 3.1 DID in BfR to 36.2 ± 6.8 DID in DuR (p < 0.001), and to 42.6 ± 5.3 DID in AfR (p < 0.001 vs. BfR). Statin consumption significantly rose from 22.0 ± 3.0 DID in BfR to 31.6 ± 6.3 DID in DuR (p < 0.001), and further to 37.6 ± 4.7 DID in AfR (p < 0.01 vs. DuR). High-intensity statin consumption elevated by 115.9% in AfR compared to baseline (p < 0.001). Prescribing of LLDs decreased from 12.5 ± 0.6 DID in BfR to 7.2 ± 1.2 DID in DuR (p < 0.001), later reached 13.6 ± 3.8 DID in AfR (p < 0.001 vs. DuR), with prescribing for ongoing users following similar trend. Expenditure on LLDs increased from €8.4 m ± 0.9 m in BfR to €11.4 m ± 2.0 m in DuR (p < 0.001) and to €12.8 m ± 1.9 m in AfR (p < 0.001 vs. BfR). Conclusions: This study revealed a surge in consumption of LLDs in Turkey following the onset of the COVID-19 pandemic. This rise might be related to practices facilitating drug access, in addition to potentially greater adherence, or the necessity for more intense pharmacotherapy due to elevated cardiovascular risk.
Keywords: COVID-19 Restrictions; Lipid-Lowering Drugs; Medication Use; Statins